SCHEMA- BROADENING INSTRUCTION IN GRADE 9 MATHEMATICS - Bien, Jennylyn B; Lucilo, Jayson A (PEOPLE: International Journal of Social Sciences, 2020)
This pre-experimental study is aimed to present the effects of using the Schema- Broadening Instruction (SBI) to the Mathematics performance of one Grade 9 class at a barangay high school in the Philippines. The study used a modified approach of SBI that adopted the use of the following visual and procedural schemes: (a) The Frayer Model; (b) Visual representations of variation equations; and (c) Polya’s Four Steps in Problem Solving. The modified approach of SBI has also incorporated the use of structured (for concept formation) and open inquiry-based (for problem solving) activities. The approach aimed to reduce the students’ cognitive load in learning Mathematics by introducing visual and procedural schemas. Schemas can be handled with very little conscious effort once acquired and automated. Hence, can reduce students’ working memory load (Ericson, 2005). Results from the study showed that the students gained a wonderful experience of learning through the modified approach of Schema-Broadening Instruction. The students also showed capabilities of learning through structured forms of activities were guide questions and steps were provided for them in generalizing the concepts of the topic. But the Grade 9 students showed unreadiness for open inquiry-based activities and were not yet capable of constructing their own procedure in problem solving. The students preferred to be guided towards the step by step solution instead. Data gathered also showed that the approach has improved the students’ conceptual understanding that lead all the students to mastery. The students’ performance under problem solving also showed improvements but was not enough for all the students to gain mastery. Future scope for the study would be to develop validated visual and procedural schemas that can further reduce cognitive overload in learning Mathematics.